ESTUDO DE CASO DE UM PACIENTE COM DOENÇA DE PARKINSON - Mertins, Simone M.; Oliveira, Daiane d.; Subutzki, Jordana; Loro, Marli M.; Kolankiewicz, Adriane C. B.; Lauter, Dagmar S. (Salão do Conhecimento, 2013)
Resumo